问题
解答题
计算题: ①(a-3b2)-4•(a-2b-3)3(结果只含正整数指数幂) ②先化简
③已知:
④解方程
|
答案
①(a-3b2)-4•(a-2b-3)3
=a12b-8•a-6b-9
=a6b-17
=
;a6 b17
②
÷2a+1 a2-1
-a2-a a2-2a+1 1 a+1
=
•2a+1 (a+1)(a-1)
-(a-1)2 a(a-1) 1 a+1
=
-2a+1 a(a+1) 1 a+1
=2a+1-a a(a+1)
=a+1 a(a+1)
=
,1 a
∵a2-1≠0,a2-a≠0,
∴a≠±1,a≠0,
∴a=4,
当a=4时,原式=
;1 4
③
=x+3 (x-2)2
+A x-2
,B (x-2)2
=x+3 (x-2)2 A(x-2)+B (x-2)2
=x+3 (x-2)2
,Ax+(-2A+B) (x-2)2
A=1,-2A+B=3,
解得:A=1,B=5;
④
+2 x+1
=3 x-1
,6 x2-1
方程两边都乘以(x+1)(x-1)得:2(x-1)+3(x+1)=6,
解这个方程得:2x-2+3x+3=6,
5x=5,
x=1,
检验:∵把x=1代入(x+1)(x-1)=0,
∴x=1是原方程的增根,
即原方程无解.